The Effectiveness of a Group Counseling Program Based on the Elective Theory in Reducing Emotional Regulation Problems and Among Mothers of Adolescents in Jordan - Khaleel, Manal Naji (Arab Journal for Sciences and Research Publishing, 2022)
The current study aimed to examining the effectiveness of a group counseling program, based on eclective theory on Reducing Emotional Regulation Problems and Improving Parental Competence Among Mothers of Adolescents in Jordan. A sample of (30) mothers were intentionally selected and then assigned to either the experimental or control group with (15) participants in each group. To achieve the goal of the study, emotion regulation difficulties scale (Bjurberg,2016) Codified by)Abadi, Sufyan and Amin,2019). The study was conducted using a Quazi experimental design, Psychometric properties of instrument was evaluated before administering it. Data analysis was completed using (ANCOVA) and (MANCOVA). Results showed statistically significant differences between the experimental and control groups in regards to the post test findings of the emotion regulation difficulties scale.Based on these findings, the principal investigator recommends the importance of building and providing psychological counseling programs based on other theories related to the category of adolescents, which contribute to helping them overcome this difficult developmental stage with their children. The study also recommended the application of the counseling program to the category fathers&teachers of adolescent.
Keywords: Group Counseling Program; Eclective Theory; Emotional Regulation Problems; Mothers of Adolescents